The effects of recovery interventions on consecutive days of intermittent sprint exercise - King, M.; Duffield, R. (The Journal of Strength and Conditioning Research, 2009)
The purpose of this study was to compare four recovery interventions following simulated team sport, intermittent-sprint exercise on consecutive days. Ten female netball players performed four randomized sessions of a simulated netball exercise circuit on consecutive days. Each condition consisted of two identical sessions (Session 1 and 2), with the recovery intervention implemented at the completion of Session 1. Participants performed all interventions involving: passive recovery, active recovery (ACT), cold water immersion (CWI) and contrast water therapy (CTWT). No significant differences (p > 0.05) were evident between conditions for exercise performance (vertical jump, 20-m sprint, 10-m sprint, total circuit time) during Session 2. Effect size data indicated trends for an ameliorated decline in 5 × 20-m sprints and vertical jump for CTWT and CWI, respectively. CTWT demonstrated a significant reduction (p = 0.04) in lactate post-intervention compared to ACT recovery. Further, ACT recovery resulted in a significantly elevated (p < 0.01) heart rate compared to all other conditions postintervention and demonstrated significantly higher (p < 0.01) rating of perceived exertion postintervention and muscle soreness pre-exercise Session 2. It is likely that while interventions may be applicable to team sport practices, the 24-hour recovery period between exercise bouts was sufficient to allow performance to be maintained, regardless of recovery interventions.